A comparison of nurse shift workers' and non‐shift workers' psychological functioning and resilience. (16th May 2019) - Tahghighi, Mozhdeh; Brown, Janie A.; Breen, Lauren J.; Kane, Robert; Hegney, Desley; Rees, Clare S.
Abstract: Aims: To investigate the impact of shift work on the psychological functioning and resilience of nurses by comparing nurses who work shifts and nurses who work regular hours. Design: A comparative descriptive design using an online self‐report questionnaire. Method: Data were collected from employed Registered and Enrolled Nurses ( N = 1, 369) who were members of the Queensland Nurses and Midwives Union (QNMU) in 2013. The survey included standardized measures of resilience, depression, anxiety, compassion satisfaction, compassion fatigue, and intention to leave the profession. Results: Generalized Linear Mixed Model analysis revealed shift workers had significantly lower levels of compassion satisfaction. However, there were no significant differences between the groups on resilience, depression, anxiety, stress, compassion fatigue or intention to leave nursing. Conclusion: The findings suggest that shift work is not associated with worse psychological functioning or lower resilience in nurses. However, this study requires replication using a longitudinal design to confirm these findings. Abstract : 目的: 通过对轮班护士和定时上班的护士之间的比较, 调查轮班制对护士心理功能和心理复原力的影响。 设计: 使用在线自我报告问卷的比较描述性设计。 方法: 数据来自2013年昆士兰护士和助产士联盟(QNMU)成员里的聘用注册护士和注册护士(人数为1369人)。这项调查包括复原力、抑郁、焦虑、同情心满意度、同情疲劳和离职打算的标准化措施。 结果: 广义线性混合模型分析显示, 轮班员工的同情心满意度明显较低。但是, 在复原力、抑郁、焦虑、压力、同情疲劳或离职意向等方面, 两组之间没有明显差异。 结论: 调查结果表明, 轮班工作与护士的心理功能变糟和复原力降低没有关系。然而, 这项研究需要使用纵向设计来证实这些发现。